The impacts of digital inclusion on the mental health and quality of life of the elderly (Research, Society and Development, 2022)
The growing and accelerated aging of the population is an undeniable reality. Enabling the access of the elderly to the digital world can be a way to improve their quality of life and a challenge for public policies of inclusion. The present work aims to analyze the impacts of digital inclusion on the mental health and quality of life of the elderly, through a literature review. The search for scientific articles was carried out in Scientific Electronic Library Online (SCIELO), Latin American and Caribbean Literature on Health Sciences (LILACS), Bireme and CAPES databases. The descriptors used were researched in the DeCS, being selected: “mental health”, “elderly”, “quality of life”, “technology”, “social media” and “senior age”. The inclusion criteria adopted were: original articles, published in Portuguese and English, in indexed journals and/or articles published in journals and published in the annals of scientific events, between 2017 and 2022. The search resulted in 883 articles. After analyzing the titles and abstracts, the final sample consisted of 8 articles. It was concluded that the population is aging significantly and that technological resources change at a very fast pace. Elderly people have a greater difficulty in adapting and keeping up with digital advances, which can be explained by the low literacy or the late access of these individuals to technology. It is essential to implement projects that allow the digital inclusion of the older population.